A Compact Slotted Patch Hybrid-Mode Antenna for Sub-6 GHz Communication - Bei Huang; Mochao Li; Weifeng Lin; Jun Zhang; Gary Zhang; Fugen Wu (International Journal of Antennas and Propagation)
A compact hybrid-mode antenna is proposed for sub-6 GHz communication. The proposed antenna is composed of a slotted rectangular patch, a feeding dipole, and a balun. Three modes are sequentially excited in a shared patch to achieve a compact size. A prototype antenna with a major size of 0.48 λ0 × 0.31 λ0 × 0.16 λ0 (λ0 is the wavelength in the free space at the center of the operating frequency band) is fabricated and measured. The measured results demonstrate an impedance bandwidth of 56.87% from 2.97 GHz to 5.33 GHz and an average gain of approximately 8.00 dBi with 1 dB variation in the operating frequency band of 3.0–5.0 GHz. The proposed antenna can be an element for microbase stations in sub-6 GHz communication.